2022
DOI: 10.17219/dmp/152071
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of monkeypox: Brief review

Abstract: The current outbreak of monkeypox infection has caught the attention of people worldwide. Updated data showed a dramatic increase in the number of patients in many non-endemic countries. An emergence of monkeypox together with coronavirus disease 2019 (COVID-19) caused a tremendous burden on the healthcare system, globally.The aim of this review was to briefly describe the current situation, transmission, clinical features, diagnosis, and prevention of the disease. Oral manifestations of monkeypox as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Interestingly, lesions may occur in the same individuals at different stages. These oral symptoms have never before been described in patients in the endemic region [ 27 ]. In a study carried out by Thornhill et al in 2022, 26 people demonstrated oropharyngeal symptoms such as oral or tonsillar lesions, odynophagia, epiglottitis, and pharyngitis as the first symptoms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lesions may occur in the same individuals at different stages. These oral symptoms have never before been described in patients in the endemic region [ 27 ]. In a study carried out by Thornhill et al in 2022, 26 people demonstrated oropharyngeal symptoms such as oral or tonsillar lesions, odynophagia, epiglottitis, and pharyngitis as the first symptoms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current pandemic manifestations have revealed characteristic of oral and oropharyngeal lesions that appear concurrently with the first skin lesions and rashes, with accompanying fever and swollen lymph nodes [ 15 ]. MPXV-positive patients may manifest vesicular or pustular lesions in the oral cavity, often with oral blisters of a spherical shape and a crimson border after breaking off the roofs of the vesicle or pustule.…”
Section: Monkeypox Virus (Mpxv)mentioning
confidence: 99%
“…The sores are initially painful and later itchy [ 16 ]. The Centers for Disease Control (CDC) has confirmed that 70% of MPXV patients had some form of mouth or tongue lesions [ 15 ].…”
Section: Monkeypox Virus (Mpxv)mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Several recent reports on MPXV-oral lesions have been published. [3][4][5][6][7][8][9][10] Two scoping reviews 3,4 and a meta-analysis 5 have provided valuable insights into the presence and clinical characteristics of MPXV-oral lesions. However, to our knowledge, information regarding the histological and ultrastructural MPVX findings in the oral mucosa is not available.…”
Section: Introductionmentioning
confidence: 99%